Gas sensor properties of zno nanorods grown by chemical bath deposition - Gasparotto, Gisane [UNESP]; Mazon, Talita; Gasparotto, Gisele [UNESP]; Zaghete, Maria Aparecida [UNESP]; Perazolli, Leinig Antonio [UNESP]; Varela, José Arana [UNESP] (Trans Tech Publications, 2014)
The present work shows a study about the growing of ZnO nanorods by chemical bath deposition (CBD) and its application as gas sensor. It was prepared ZnO nanorods and Au decorated ZnO nanorods and the samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and gas sensing response measurements. The results obtained by XRD show the growth of ZnO phase. It was possible to observe the formation of uniform dense well-aligned ZnO nanorods. The results obtained also revealed that Ag nanoparticles have decorated the surface of ZnO nanorods successfully. Au nanoparticles with diameter of a few nanometers were distributed over the ZnO surface nanorods. The gas sensing response measurements showed a behavior of n type semiconductor. Furthermore, the Au-functionalized ZnO nanorods gas sensors showed a considerably enhanced response at 250 and 300 °C.
Keywords: Chemical Bath Deposition; Gas Sensor; Nanorods; ZnO